Broom as Attribute of Traditional Russian Wedding in Udmurt Republic - S. V. Tolkachova (Научный диалог)
The article is devoted to peculiarities of the symbolism and ritual functioning of one of the attributes of the Russian wedding rituals of modern Udmurt Republic - a broom. The elements of the wedding ritual in which a broom was used as a ritual object are characterized. Dialectal nominations of ritual action with the broom are given. Features of the functions of this wedding item are summarized. It is shown that sweeping with a broom on the second or third day of the wedding symbolically marked the completion of the spatial transition of the bride and bringing her to the family of the husband. It is noted that the broom performed mediation function in the wedding divinations, and in customs of “riding the brooms” and “whipping mummers.” It is indicated that the purifying function of a broom in a traditional wedding ceremony of the Russian population of Udmurtia was manifested at the level of symbols and at the household level. Distant semantics of a broom is considered on the example of the description of the custom of “dispersing broom,” recorded by V. G. Boldyreva. It is shown that some other wedding attributes have similar functions. There is a significant degree of variation in symbolic content and ritual status of a broom, depending on the dialect and folklore traditions, kind of wedding episode and the purpose of its commission.